Crop rotation increases root biomass and promotes the correlation of soil dissolved carbon with the microbial community in the rhizosphere - Chen, Shuaimin; Yao, Fanyun; Mi, Guohua; Wang, Lichun; Wu, Haiyan; Wang, Yongjun (Frontiers in Bioengineering and Biotechnology, 2022)
As essential approaches for conservation agricultural practices, straw residue retention and crop rotation have been widely used in the Mollisols of Northeast China. Soil organic carbon, root development and the microbial community are important indicators representing soil, crop and microbiota, respectively, and these factors work together to influence soil fertility and crop productivity. Studying their changes and interactions under different conservation practices is crucial to provide a theoretical basis for developing rational agricultural practices. In the present study, an experiment was conducted using the conventional practice (continuous maize without straw retention, C) and three conservation practices, namely, continuous maize with straw mulching (CS), maize–peanut rotation (R), and maize–peanut rotation with straw mulching (RS). Straw mulching (CS) significantly increased soil total organic carbon (TOC), active organic carbon (AOC), and microbial biomass carbon (MBC), but did not promote maize yield. Maize–peanut rotation (R and RS) significantly increased dissolved organic carbon (DOC) in the rhizosphere by promoting root growth and maize yield (increased by 10.2%). For the microbial community structure, PERMANOVA and PCoA indicated that the bacterial community differed significantly between rhizosphere soil and bulk soil, but the fungal community shifted more under different agricultural practices. The correlation analysis indicated that the rotation system promoted the association between soil DOC and the microbial community (especially the bacterial community), and straw mulching enhanced the connection between TOC and the fungal community. Some plant growth–promoting rhizobacteria (including Bacillus, Streptomyces, Rhizobium, and Pseudomonas) were enriched in the rhizosphere soil and were increased in the rotation system (R and RS), which might be due to an increase in the soil rhizosphere DOC level. These beneficial microbes had significantly negative correlations with several fungal groups (such as Mycosphaerella, Penicillium, Paraphoma and Torula) that were classified as plant pathotrophs by FUNGuild. These results indicated that ensuring plant root development and improving root–bacteria interactions are of great importance to guarantee crop yield when implementing conservation tillage practices.